2022
DOI: 10.30935/cedtech/11812
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Learning Losses of Students During the COVID-19 Pandemic

Abstract: The COVID-19 outbreak has wreaked havoc on educational systems on a scale never seen before in history. The closure of schools and other institutions of learning has impacted 94% of the world's student population. Even school closures, such as those that occur during the summer, have a significant effect on children's academic ability. The word "learning loss" refers to any loss of information and abilities, whether specific or generic. By Fall 2020, extended absences from school will have a detrimental effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Most students use their smartphones to have fun, stay in touch with friends and learn (Singh & Samah, 2018). There are studies that claim using smartphones has a good influence on students' learning (Ahmed et al, 2020;Tao et al, 2018;Zhdanov et al, 2022), but there are other studies that claim it has a detrimental effect on students' learning (Faimau et al, 2022;Foen Ng et al, 2017;Junco, 2012;Platonova et al, 2022). The study's data were aggregated based on the random effect you.…”
Section: Discussionmentioning
confidence: 99%
“…Most students use their smartphones to have fun, stay in touch with friends and learn (Singh & Samah, 2018). There are studies that claim using smartphones has a good influence on students' learning (Ahmed et al, 2020;Tao et al, 2018;Zhdanov et al, 2022), but there are other studies that claim it has a detrimental effect on students' learning (Faimau et al, 2022;Foen Ng et al, 2017;Junco, 2012;Platonova et al, 2022). The study's data were aggregated based on the random effect you.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies focused on the positive or negative effects of homework on science education and provide explanations about the sources of these effects (Chen et al, 2022;Dolean & Lervag, 2022;Fan et al, 2022;Haq et al, 2020;Kukliansky et al, 2016;Kurt & Tas, 2019;Mešić et al, 2021;Oschepkov et al, 2022;Qarkaxhja et al, 2021;Ratniyom et al 2016;Salame & Hanna, 2020;Uanhoro & Young, 2022;Yildiz & Sahin, 2017;Zhdanov et al, 2022).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Some of these studies are related to environmental awareness and attitudes toward the environment. Many studies investigating attitudes towards the environment showed that most of the participants develop positive attitudes toward environment (Adanali & Mete, 2019;Dolenc Orbanic & Kovac, 2021;Durmus & Kinaci, 2021;Miyaji & Fukui, 2020;Molefe & Aubin, 2021;Ozonur, 2021;Shagiakhmetova et al, 2022;Zhdanov et al, 2022). Some studies have investigated the relationship between environmental education and some variables that may be related to it.…”
Section: Introductionmentioning
confidence: 99%